EFFECT OF STIMULATORS ON THE NUMBER OF LEAVES OF MUNGBEAN VARIETIES - S.Sh.Khayrullaev1, O.B.Choriev2, S.X.Zokirov3 (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This article provides data on the effect of stimulants on the number of leaves of mung bean varieties. According to it, the best indicators were found when the number of leaves increased when Fitovak and Hosildor stimulants were applied to the Barqaror and Durdona varieties at 1.05 and 1.15 l/ha, respectively.